Green synthesis of silver nanoparticles using aqueous fruit peel extract of citrus aurantifolia: optimization, its characterization and stability test - Nabila Adlina Nasruddin; Nur Raihana Ithnin; Hidayatulfathi Othman; Zatul-’Iffah Abu Hasan; Norashiqin Misni (Penerbit Universiti Kebangsaan Malaysia, 2024)
In this present study, silver nanoparticles were synthesized by green biological synthesis method using plant extract from fruit peel of Citrus aurantifolia as reducing agents. All the parameters in the synthesis of silver nanoparticles (AgNPs) were optimized to achieve a better yield, controlled size and stability of the particles. The biosynthesis of silver nanoparticles was monitored via UV-vis spectrophotometer and stability test was done. The resulting UV-Vis spectra of synthesized AgNPs from C. aurantifolia fruit peel extract (CAFPE) showed standard surface plasmon resonance band at 420 nm which indicated the presence of AgNPs. The optimum result was obtained with an optimum concentration at 4 mM AgNO3 , leaving in a dark room temperature for 24 h and using a concentration 1:3 ratio (extract: silver nitrate). Moreover, the stability of the CAFPE-AgNPs was also observed after 30 days of synthesis and even up to 10 months, indicating optimization plays major role towards the stability fate of nanoparticles. The FTIR analysis showed possible functional groups of biomolecules that play roles in the bioreduction and capping of silver nanoparticles. In addition, it is believed that these parameters are highly suitable for bulk production of single spherical AgNPs with diameter 29.6- 45.2 nm confirmed via FESEM. Thus, the obtained results clearly suggest that optimization of silver nanoparticles may have important role in attaining a better yield and stability of metal nanoparticles, refraining back to its original structure or particles.